Volatile constituents of essential oils isolated from leaf and inflorescences of Piper longum Linn. (Chittagong University Journal of Biological Sciences, 2013)
Essential oil compositions of the inflorescences and leaf of Piper longum Linn. were investigated by gas chromatographymass spectrometry (GC-MS). P. longum oils were found to contain few monoterpene hydrocarbons, a moderate content of sesquiterpenes and high content of aliphatic hydrocarbons. The inflorescences oil rich in eugenol (33.11%), caryophyllene (9.29%), cinnamyl acetate (5.91%) and b-pinene (4.74%), whereas leaf oil rich in trans-nerolidol (19.08%), caryophyllene (12.25%), 3-heptene, 7-phenyl- (3.71%), benzyl benzoate (3.68%), caryophyllene oxide (3.62%) and ?-elemene (3.28%). The compositions of both oils varied qualitatively and quantitatively. DOI: http://dx.doi.org/10.3329/cujbs.v3i1.13408 The Chittagong Univ. J. B. Sci.,Vol. 3(1&2):77-85, 2008